Investigating Subantarctic 14C Ages of Different Peat Components: Site and Sample Selection for Developing Robust Age Models in Dynamic Landscapes. Issue 4 (10th June 2019) - Thomas, Zoë A; Turney, Chris S M; Hogg, Alan; Williams, Alan N; Fogwill, Chris J
ABSTRACT: Precise radiocarbon ( 14 C) dating of sedimentary sequences is important for developing robust chronologies of environmental change, but sampling of suitable components can be challenging in highly dynamic landscapes. Here we investigate radiocarbon determinations of different peat size fractions from six peat sites, representing a range of geomorphological contexts on the South Atlantic subantarctic islands of the Falklands and South Georgia. To investigate the most suitable fraction for dating, 112 measurements were obtained from three components within selected horizons: a fine fraction <0.2 mm, a coarse fraction >0.2 mm, and bulk material. We find site selection is critical, with locations surrounded by high-ground and/or relatively slowly accumulating sites more susceptible to the translocation of older carbon. Importantly, in locations with reduced potential for redeposition of material, our results show that there is no significant or systematic difference between ages derived from bulk material, fine or coarse (plant macrofossil) material, providing confidence in the resulting age model. Crucially, in areas comprising complex terrain with extreme relief, we recommend dating macrofossils or bulk carbon rather than a fine fraction, or employing comprehensive dating of multiple sedimentary fractions to determine the most reliable fraction(s) for developing a robust chronological framework.